2011
DOI: 10.1186/1475-2859-10-109
|View full text |Cite
|
Sign up to set email alerts
|

Production in yeast of pseudotype virus-like particles harboring functionally active antibody fragments neutralizing the cytolytic activity of vaginolysin

Abstract: BackgroundRecombinant antibodies can be produced in different formats and different expression systems. Single chain variable fragments (scFvs) represent an attractive alternative to full-length antibodies and they can be easily produced in bacteria or yeast. However, the scFvs exhibit monovalent antigen-binding properties and short serum half-lives. The stability and avidity of the scFvs can be improved by their multimerization or fusion with IgG Fc domain. The aim of the current study was to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…The vector pFX7, without any insert or constructed plasmids, pFX7-KIPyV-VP1, pFX7-WUPyV-VP1, pFX7-MCPyV-VP1, pFX7-HPyV6-VP1, pFX7-HPyV7-VP1, pFX7-TSPyV-VP1, pFX7-HPyV9-VP1, pFX7-HPyV10-VP1, pFX7-STPyV-VP1, pFX7-HPyV12-VP1n 380 , pFX7-HPyV12-VP1s 380 , pFX7-HPyV12-VP1n 364 , pFX7-HPyV12-VP1s 364 , and pFX7-NJPyV-VP1 were transformed into the S. cerevisiae strain, AH22-214 ( a, leu2-3,112, his4-519 ). The growing conditions for yeast transformants harboring plasmids with VP1-encoding genes from different HPyVs and conditions for induction of VP1 synthesis were similar to that previously described [ 75 ]. Briefly, yeast cells were first cultured in glucose- then galactose-containing induction media for 24 and 18 h, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vector pFX7, without any insert or constructed plasmids, pFX7-KIPyV-VP1, pFX7-WUPyV-VP1, pFX7-MCPyV-VP1, pFX7-HPyV6-VP1, pFX7-HPyV7-VP1, pFX7-TSPyV-VP1, pFX7-HPyV9-VP1, pFX7-HPyV10-VP1, pFX7-STPyV-VP1, pFX7-HPyV12-VP1n 380 , pFX7-HPyV12-VP1s 380 , pFX7-HPyV12-VP1n 364 , pFX7-HPyV12-VP1s 364 , and pFX7-NJPyV-VP1 were transformed into the S. cerevisiae strain, AH22-214 ( a, leu2-3,112, his4-519 ). The growing conditions for yeast transformants harboring plasmids with VP1-encoding genes from different HPyVs and conditions for induction of VP1 synthesis were similar to that previously described [ 75 ]. Briefly, yeast cells were first cultured in glucose- then galactose-containing induction media for 24 and 18 h, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant VP1 protein purification was carried out as previously described [ 75 ]. Briefly, yeast cells containing recombinant VP1 protein were suspended in DB450 buffer (450 mM NaCl, 1 mM CaCl 2 , 0.001 % 0.25 M L-Arginine, and Trition X-100, in 10 mM Tris/HCl-buffer, pH 7.2) with 2 mM PMSF and EDTA-free Complete Protease Inhibitor Cocktail tablets (Roche Diagnostics, Mannheim, Germany), and then were homogenized with glass beads using Bead-Beater GB26 (BioSpec Products, Inc., Bartlesville, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 ). Such structures represent multivalent antibody nanoparticles possessing strong antigen-binding and -neutralizing activities that effectively prevented mammalian cell lysis induced by vaginolysin [ 56 ]. Another approach considers the Saccaromyces display of scFvs fused to non-self-cleaving Mxe GyrA intein for promoting the chemical functionalization of the antibody fragment by exploiting the Expressed Protein Ligation methodology.…”
Section: Eukaryotic Expression Systems For Antibody Fragmentsmentioning
confidence: 99%
“…Hamster polyomavirus (HaPyV) VP1 protein has been exploited for the generation of either chimeric VLPs harbouring foreign epitopes, or pseudotype VLPs when co-expressed with the minor capsid protein VP2 that binds within the central 5-fold cavity of each VP1 pentamer [ 8 11 ]. Moreover, it was demonstrated that HaPyV-derived pseudotype VLPs represent an efficient carrier for functionally active complex molecules, such as antibodies [ 12 ]. In these pseudotype VLPs, an intact VP1 protein is functioning as a carrier mediating VLP formation of both VP1 and the modified VP2 protein molecule.…”
Section: Introductionmentioning
confidence: 99%